2019
DOI: 10.37897/rmj.2019.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpigmentation and ACTH – an overview of literature

Abstract: Hyperpigmentation and aCtH -an overview of literature assist. prof. florica Sandru 1,2 , md, phd, lecturer mihai Cristian dumitrascu 2,3 , md, phd, assist. prof. Simona elena albu 2,3 , md, phd, lecturer mara Carsote 2,4 , md, phd, lecturer ana valea 5,6 , md, phd ABSTRACT Introduction. ACTH (adrenocorticotropic hormone) is a key regulator of adrenal production involving cortisol as an essential hormone for life. The melanin is a pigment which is produced by melanocytes at the level of melanosomes (the melanog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…The effects of the gestational period on the ACTH ratios indicate a significant increase of ACTH level in the third trimester compared with the first trimester. This result in agreement with previous studies (Sandru et al, 2019;Karaca et al, 2010;Lindsay and Nieman, 2005), summarising that women of childbearing age tend to have larger glands, and upward convexity of the pituitary gland causes increased ACTH releasing, also include placental synthesis and release of biologically active CRH and ACTH. Furthermore, they found a positive correlation has observed between CRH and POMC; Proopiomelanocortin (POMC) is the polypeptide precursor of ACTH, which is physiologically present in blood originate from the anterior pituitary.…”
Section: 2hormonal Analysis 421 Acthsupporting
confidence: 93%
See 2 more Smart Citations
“…The effects of the gestational period on the ACTH ratios indicate a significant increase of ACTH level in the third trimester compared with the first trimester. This result in agreement with previous studies (Sandru et al, 2019;Karaca et al, 2010;Lindsay and Nieman, 2005), summarising that women of childbearing age tend to have larger glands, and upward convexity of the pituitary gland causes increased ACTH releasing, also include placental synthesis and release of biologically active CRH and ACTH. Furthermore, they found a positive correlation has observed between CRH and POMC; Proopiomelanocortin (POMC) is the polypeptide precursor of ACTH, which is physiologically present in blood originate from the anterior pituitary.…”
Section: 2hormonal Analysis 421 Acthsupporting
confidence: 93%
“…Results show a highly significant elevation in serum ACTH levels of first, second, and third trimesters in normal Kurdish primigravida pigmented ladies when compared with ACTH levels of non-pigmented healthy women, the present result in agreement with (Sandru et al, 2019;Maranduca et al, 2019;Sanson et al, 2003) they showed that ACTH levels increased throughout pregnancy reaching maximum levels during the third trimester. There is agreement that the proopiomelanocortin (POMC) peptides with huge melanogenic action are ACTH α-MSH, and β-MSH.…”
Section: 2hormonal Analysis 421 Acthsupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, hypothalamic corticotropin-releasing hormone (CRH) stimulates POMC gene expression in the pituitary gland, most of its actions being mediated by CRF1R and CRF2R receptors; CRH expression and its receptors in addition to POMC expression have also been identified in skin and mucosa, confirming a complex interaction between glucocorticoid axes and the cutaneomucosal system [ 15 ]. Conditions with POMC- and ACTH-associated pigmentation lesions include AD and Nelson’s syndrome (which develops in Cushing’s disease after bilateral adrenalectomy—typically a last option of therapy when all the other well-known methods have been unsuccessful), both of them underlying pituitary ACTH anomalies, while nonpituitary ACTH disorders include paraneoplastic (ectopic) Cushing’s syndrome, which particularly accompanies some types of neuroendocrine neoplasia and lung cancers that may produce abnormal ACTH with skin actions [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Excess adrenocorticotrophic hormone (ACTH) levels are seen in three situations – Addison disease, Cushing disease and syndrome, and Nelson syndrome, all of which are characterized by cutaneous hyperpigmentation due to stimulation of melanogenesis by increased ACTH. [ 93 ] Hyperpigmentation of the skin is a hallmark and the earliest feature of Addison disease. The 'Addisonian' hyperpigmentation has certain characteristics such as a) involvement of sun-exposed areas; b) involvement of bony prominences and pressure points like knuckles [ Figure 15a ], knees, elbows, waist line and underneath the brassier straps; c) darkening of the normally pigmented areas such as areola, nipples, axillae, groins, and perineum; d) darkening of the pigmented lesions such as café au lait macules and melanocytic nevi; e) pigmentation of the nails (longitudinal melanonychia) and palmar creases; and f) pigmentation of the scars developing after the disease onset.…”
Section: Pigmentary Lesionsmentioning
confidence: 99%